Theodor Heuss, Erzieher zur Demokratie - Heuss, Theodor (Briefe, 2007)
Theodor Heuss is one of the most significant founders of German politics' new political beginning in Germany. As a liberal party politician and leader of the Württemberg-Baden Kultministerium (ministry of culture) he gained respect in all four occupied zones. He faced his most important task during 1948/49 in the Parlamentarischer Rat (parliamentary council), where he made an essential contribution to the creation of the constitution. Both as a journalist and an educator for democracy, Heuss advocated a moral reformation and the ruthless examination of crimes committed by the German people under the National Socialist regime.